The Progressive wave in Latin America: Argentina, Brazil, Colombia, Mexico, the steep path to structural reform - Salama, Pierre (Argumentum, 2023)
Following the economic, environmental and social failures of the Right-wing in power, which, in Brazil, was the Extreme Right, which also weakened the institutions of power, almost all countries are returning to a Progressive wave. This wave differs, sometimes profoundly, in its aims, from country to country. What primarily unites them is their rejection of the painful past experiences, followed by a set of hopes, some for of a better society, others for of a profoundly different society. If utopia is the condition of the movement, if the dream is necessary, if asking for the impossible is to be realistic, it is more than ever necessary to determine the anatomy of the structural problems experienced by the economies of every country. This would allow the course of events to be influenced, and open new pathways which, although precarious, would overcome economic and social difficulties. Latin American countries are on a knife edge, but it is not the same for each of them, even though this “razor’s edge” has common characteristics. Four countries are highlighted in this article: Argentina, Brazil, Colombia and Mexico.